Working With Infertile Couples Seeking Assisted Reproduction: An Interpretative Phenomenological Study With Infertility Care Providers - Facchin, Federica; Leone, Daniela; Tamanza, Giancarlo; Costa, Mauro; Sulpizio, Patrizia; Canzi, Elena; Vegni, Elena (Frontiers in Psychology, 2020)
Although most studies investigated the impact of infertility and its treatment on the couple, a small body of evidence suggested that infertility care providers may experience different sources of stress related for instance to excessive workload, the complexity of the technique, and relational difficulties with patients. The current study aimed at providing further insight into the understanding of the subjective experience of infertility care providers by highlighting their feelings and emotions, personal meanings, challenges, and opportunities. Following the methodological guidelines of Interpretative Phenomenological Analysis, we conducted individual semi-structured interviews with 23 members of two different fertility units. Interviews were audiotaped and transcribed verbatim. Textual analysis was then conducted to identify emerging dominant themes and subthemes. Three main themes were extracted: (i) dealing with infertile patients and their specificities, (ii) performing assisted reproductive technology (ART), (iii) being part of a team. These themes related to participants experiencing: (i) difficulties in establishing an empathic connection and communicating with couples, such that women were sometimes perceived as “particular patients” and men as poorly involved in the process; (ii) difficulties in dealing with a complex procedure in which errors are not allowed (as reported by embryologists), with a growing number of women aged > 40 seeking assisted reproduction, despite the risks for their health; (iii) being part of a team as a resource, although the huge amount of time spent together can involve conflicts and organizational problems. These findings suggested that patients’ overpersistence (rather than just dropout) represents an important source of stress for infertility care providers. At the same time, the concept of particular or difficult patient derives from the combination of multiple factors, including providers’ own history and subjective experience. The presence of mental health professionals in fertility units is essential to help providers improve the quality of doctor-patient communication and relieve the stress related to organizational issues and conflicts.